Helical Colloidal Sphere Structures through Thermo‐Reversible Co‐Assembly with Molecular Microtubes1. Issue 12 (25th February 2013) - Jiang, Lingxiang; de Folter, Julius W. J.; Huang, Jianbin; Philipse, Albert P.; Kegel, Willem K.; Petukhov, Andrei V.
<x xml:space="preserve">Abstract</x> The co‐assembly of spherical colloids and surfactant–cyclodextrin microtubes yields a library of dynamic colloid‐in‐tube structures, including helices. In situ observations of these structures, including their thermo‐reversible assembly and disassembly, demonstrate the potential of the interplay between molecular and colloidal self‐assembly, thereby providing a novel route to temperature‐sensitive particle alignment and release.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>